TransLeish: Identification of membrane transporters essential for survival of intracellular Leishmania parasites in a systematic gene deletion screen - Albuquerque-Wendt, A; McCoy, C; Neish, R; Dobramysl, U; Alagöz, Ç; Beneke, T; Cowley, SA; Crouch, K; Wheeler, RJ; Mottram, JC; Gluenz, E (Nature Research, 2025)
For the protozoan parasite Leishmania, completion of its life cycle requires sequential adaptation of cellular physiology and nutrient scavenging mechanisms to the different environments of a sand fly alimentary tract and the acidic mammalian host cell phagolysosome. Transmembrane transporters are the gatekeepers of intracellular environments, controlling the flux of solutes and ions across membranes. To discover which transporters are vital for survival as intracellular amastigote forms, we carried out a systematic loss-of-function screen of the L. mexicana transportome. A total of 312 protein components of small molecule carriers, ion channels and pumps were identified and targeted in a CRISPR-Cas9 gene deletion screen in the promastigote form, yielding 188 viable null mutants. Forty transporter deletions caused significant loss of fitness in macrophage and mouse infections. A striking example is the Vacuolar H+ ATPase (V-ATPase), which, unexpectedly, was dispensable for promastigote growth in vitro but essential for survival of the disease-causing amastigotes.